Deuterium retention in tungsten and reduced activation steels after 3 MeV proton irradiation. (May 2020) - Möller, S.; Krug, R.; Rayaprolu, R.; Kuhn, B.; Joußen, E.; Kreter, A.
Highlights: 3 MeV protons used for up to 0.9 DPA damage in W and steels. PSI-2 D2 plasma exposures and subsequent µNRA retention analysis of irradiated samples. Retention increase saturates above 0.2 DPA in W and steels. Up to 3.2 atom% D in W and 0.08 atom% D in steel. Potentially critical retention for ITER W divertor in D-T phase predicted. Abstract: Nuclear fusion plasma-facing materials (PFM) will suffer from irradiation, leading to significant changes in the material properties. This study investigates the impact of displacement damage on the deuterium retention near room temperature. ITER grade tungsten, Eurofer-97, and HiperFer 17Cr5 steel samples are irradiated with a tandem accelerator with 3 MeV protons at currents of 100–600 nA on 250–550 µm spots at 320±10 K. In total 33 spots from 0 to 0.9 displacements per atom (DPA) at 0–4 µm depth are irradiated on 5 samples. After irradiation, the samples are exposed to D2 plasmas with a peak ion-flux of 2.1 × 10 21 D/m²s for 4 h at <420 K in PSI-2. Lastly, D retention is measured via 3 He nuclear reaction analysis with a spot size of 200 µm up to 4.5 µm depth. The long-term D retention in both W and steel increases with DPA with a saturation starting around 0.2 DPA. Retention in W increased by a factor 12 with up to 3.2 at.% D, while in steel increases up to 180 times with up to 0.08 at.% D were observed. The results highlight the importance of using steels also in PFMs. Compatibility of the results with heavy ion irradiations boosts the confidence in inter-comparability between different ion types, but also between ions and neutrons.